Business model stakeholders and boundary reconstruction of 5GtoB - Ming WAN (Dianxin kexue)
The advent of the 5GtoB era has brought new opportunities and development to various industries, digitization, networking and intelligence have almost become an inevitable direction for the development of all industries.In such an era, the stakeholders of the business model are facing both opportunities and challenges at the same time.The stakeholders of various business models in the development process of 5G based on the characteristics of 5G technology and industry development trends were analyzed firstly.Based on the discussion and analysis of the business boundaries of various stakeholders, the following conclusions that in the 5GtoB field were summarized, the boundaries of all business model stakeholders are being restructured, expanding outward based on the original business role positioning.It is further proposed that becoming an industry solution provider will be one of the ultimate goals of this boundary reconstruction activity.At the same time, this restructuring of the boundaries of business roles also brings new challenges to business model innovation.